2010
DOI: 10.3892/or_00000882
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of S100A6 in oral squamous cell carcinoma

Abstract: Abstract.We previously established an in vitro cellular carcinogenesis model of oral squamous cell carcinoma (OSCC) with a line of human immortalized oral epithelia cells (HIOECs), a line of cancerous HB96 cells, and other cells (HB56 cells) at the early stage of carcinogenesis. In this study, comparative proteomic analysis identified a panel of differentially expressed proteins among these cells, and S100A6 was shown as one of the significantly downregulated proteins accompanying cellular transformation. S100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, the expression and role of S100A6 in cancer cells have not been extensively studied [ 32 ]. It has been reported that S100A6 is over-expressed and associated with disease development and malignant progression in gastric cancer [ 33 ], pancreatic cancer [ 34 ], and colon cancer [ 35 ] but under-expressed in prostate cancer [ 36 ] and oral cancer [ 37 ]. However, the expression of S100A6 in breast cancer is not yet conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression and role of S100A6 in cancer cells have not been extensively studied [ 32 ]. It has been reported that S100A6 is over-expressed and associated with disease development and malignant progression in gastric cancer [ 33 ], pancreatic cancer [ 34 ], and colon cancer [ 35 ] but under-expressed in prostate cancer [ 36 ] and oral cancer [ 37 ]. However, the expression of S100A6 in breast cancer is not yet conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Since there have only been a handful of relevant studies to date, we classify them here. Western blot analysis and realtime PCR results have shown that S100A6 protein and mRNA levels are reduced in vitro and in vivo upon carcinogenesis of oral squamous cell carcinoma (OSCC) [90]. Doxorubicin has been shown to induce the expression of miR-21-5p in mesenchymal stem cells and their derived exosomes (MSC-Exo) and then regulates S100A6 to induce breast cancer cell resistance to chemotherapy [91].…”
Section: S100a6 In Other Tumorsmentioning
confidence: 99%